The drug dependency issue. An all-encompassing overview - Nizama Valladolid, Martín (1992)
From the standpoint of an overall view, people are led into the controversial problem of addiction, the first step is to clear away the main scientific and social prejudices that distort the true visualization of this phenomenom, these prejudices  have an unsteadying influence in the handling of this problem in the health area and are further damaging to the community.  In addition, the definition of the OMS (CIE-10 Borrador) is ordered and organized, and from an ecological point of view we propose an etiological model be used. We also want to attack the national and international way that the drug problem is outlined, further, we want to clearly visualize the social and family environment of the patient. The psychopathology should be systematized both from the standpoint of the family environment as well as from the standpoint of the addict himself and his history of addiction.  From the ecological (environmental) point of view, the need to rescue the addiction situation and place it in the psychiatric area. Further, the attack on addiction by preventive therapy is transdisciplinary, and the family participates in the various preventive therapy work. This is mainly educational and, in many cases, re-educational. Finally, there are six related proposais which we make in order to attack the problem correctly in the health area.